Statistical Analysis of the Financial Sector of Ukraine in the Conditions of War - Motoryn, R. M.; Prykhodko, К. R.; Momotiuk, L. Ye. (Statistics of Ukraine, 2025)
The article examines the impact of the war on the financial sector of Ukraine, systematizes the mechanisms of manifestation of this impact. The features of the impact of the war on the financial sector of Ukraine are revealed using the methodological capabilities of the system of national accounts. Since, according to the methodology of the system of national accounts, the financial sector mainly includes banks, including the central bank, as well as insurance companies, attention is focused on these institutional units. The continuation of the war exacerbates most of the risks. The largest of them, credit risk, is already being realized, and losses from it will grow in the future. Financial institutions are gradually recognizing credit losses and reflecting the impact of negative events on asset quality. Limited demand for loans, especially from households, deterioration in portfolio quality and increased provisioning increase profitability risks. The dynamics of the ratio of the volume of loans, bank deposits and other indicators of the financial system of Ukraine are analyzed. The role of bank lending in combating the consequences of military aggression is revealed and measures aimed at mitigating its negative impact on the economy are justified. An analysis of the dynamics of indicators of non-bank financial institutions was also conducted. Unlike banks, part of the market did not cope with operational risks: financial institutions stopped work, processes were disrupted, information was lost. The volume of operations of non-bank financial institutions decreased significantly. Demand for insurance and lending fell, the quality of the loan portfolio of credit unions and financial companies is deteriorating. The insurance market is working. The war became a catalyst that showed the real state of affairs of each insurer. Financially stable companies continue their activities and are being tested by war. Despite the reduction in the number of insurance companies, they are generally going through the crisis successfully. But the realities of war are forcing insurers to look at new products. Measures aimed at improving the state of the financial sector of Ukraine are justified.